Curriculum and Learning Methods Balance in Strengthening Tafaqquh fi Ad-Din in Pesantren-Based Madrasah - Annas, Azwar; Hamid, M. Abdul; Mubaligh, Ahmad (Program Studi Pendidikan Agama Islam, 2025)
The purpose of writing this article is to scrutinize the curriculum and learning methods in pesantren (Islamic boarding school)-based madrasahs in order to accomplish tafaqquh fi ad-din for students. This article also aims to identify the portion and balance between religious and general materials in the applied curriculum structure. In addition, this study explores the learning methods employed and their effectiveness in reinforcing an in-depth understanding of religion. The locus of the research is in Madrasah Aliyah Qudsiyyah Putri, a pesantren based madrasah. The approach used is qualitative with a case study design and descriptive analysis type. Data collection techniques encompass observation, interviews, and documentation. The findings of the study show that Madrasah Aliyah Qudsiyyah Putri creates a balanced curriculum between religious and general education, which seeks to produce graduates who are intellectually intelligent and have noble morals. By integrating modern approaches, yellow books, and technology, this pesantren shapes students who are ready to face the challenges of the times and become agents of social change.